2005
DOI: 10.1097/01.brs.0000175188.05542.a9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Amicar in Decreasing Perioperative Blood Loss in Idiopathic Scoliosis

Abstract: Amicar appears highly effective in decreasing perioperative blood loss. This results in less autologous blood donation, blood transfusion, costs, and complications. Its mechanism of action is uncertain but may be related to increased fibrinogen secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…Blood conservation techniques have also been extensively studied. Among the strategies that have been investigated include the usage of autologous blood transfusion, [25][26][27] cell salvage, 28 and the usage of various pharmacological agents like esmolol, 29 tranexemic acid, 30,31 amicar, 32,33 aprotinin, 34,35 and epsilon aminocaproic acid 36,37 to reduce blood loss. Two popular strategies that are frequently employed in PSF for AIS are ANH and ICS techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Blood conservation techniques have also been extensively studied. Among the strategies that have been investigated include the usage of autologous blood transfusion, [25][26][27] cell salvage, 28 and the usage of various pharmacological agents like esmolol, 29 tranexemic acid, 30,31 amicar, 32,33 aprotinin, 34,35 and epsilon aminocaproic acid 36,37 to reduce blood loss. Two popular strategies that are frequently employed in PSF for AIS are ANH and ICS techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Antifibrinolytic drugs are widely used, particularly in cardiac and orthopedic surgery, and previous reviews have found them to be effective in reducing blood loss, the need for transfusion, and even the number of reoperations for continued or recurrent bleeding. 47 The use of EACA in our institution has also shown a statistically lower intraoperative estimated blood loss, a total perioperative blood loss (including through the chest tube and Hemovac), and transfusion requirements. However, EACA has a manufacturer-reported risk of causing intracranial hypertension, although this has never been published in neurosurgical, cardiac, orthopedic, or general surgical literature after the intraoperative use of EACA.…”
Section: 45mentioning
confidence: 72%
“…Our experience includes a prospective preliminary study, a randomized double-blinded study, a fibrinogen study, and anterior and posterior spinal fusion studies, as well as a study on neuromuscular disorders. 13,47 However, the serum fibrinogen levels were found to be significantly elevated above normal in the initial 2 weeks after administration of aminocaproic acid. 46,47 Thompson et al 46 had reported that the postoperative fibrinogen levels in the serum of 57 consecutive patients with idiopathic scoliosis increased gradually and substantially from Day 1 to Day 5 after surgery, despite stopping EACA at the end of surgery.…”
Section: 45mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on the efficacy of Amicar in decreasing perioperative blood loss in idiopathic scoliosis. [17][18][19] We have found no difference in the estimated anterior intraoperative blood loss if Amicar was administered before or after the anterior procedure. 17 We now recommend that Amicar be started before the posterior spinal fusion.…”
Section: Methodsmentioning
confidence: 99%